Penegakkan Hukum Angkutan Umum Dalam Trayek di Wilayah Administrasi Kota Jambi - Imam Budy Prastiyo (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2024)
Law Number 22 of 2009 on Traffic and Road Transportation establishes safety, security, comfort, and affordability standards for public transportation in Indonesia. There are 5,349 transportation companies operating. In 2021, long-distance buses (AKAP) reached 13,510 units, with a 2.34% increase. Violations in public transportation operations still occur, such as the lack of operating permits, supervision cards, vehicle inspection books, and route deviations. There were 4,266 violations involving buses in 2021. This legal study is an empirical research that analyzes how the law operates within society, including implementation, compliance, and law enforcement. Research data were obtained from BPTD Jambi reports and legal literature, using a qualitative descriptive analysis method. This research discusses transportation implementation provisions, law enforcement, legal accountability, and efforts to optimize public transportation laws. In the administrative area of Jambi city in 2022, 14 transportation units (27%) violated operational legality aspects. Legal consequences for these violations are regulated in Law 22/2009 with criminal provisions. Thus, efforts are needed to enhance the effectiveness of public transportation law enforcement.